Physicochemical properties and periodontal ligament stem cell response to NeoMTA 2 - Ferraz, Danilo Cassiano [UNESP]; Pinto, Jáder Camilo [UNESP]; Letra, Ariadne; Silva, Renato Menezes; de Souza, Letícia Chaves; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Springer Nature, 2025)
ObjectivesTo investigate the physicochemical properties and cellular response of NeoMTA 2 as an endodontic sealer (NMTA2S) and root repair material (NMTA2R) compared to BioRoot RCS (BIR) and MTA Repair HP (MTAHP).Materials and methodsSetting time, flow, radiopacity, and solubility were evaluated based on ISO 6876/2012 standards. Volumetric change was measured using micro-computed tomography. Periodontal ligament stem cells (PDLSCs) were used for cell viability and messenger RNA expression assays.ResultsNMTA2S had longer setting time than BIR (p < .05), while NMTA2R set longer than MTAHP (p < .05). All materials met ISO 6876 standards for radiopacity and flow, with similar solubility between NMTA2S and BIR, or NMTA2R and MTAHP (p > .05). NMTA2S decreased in volume, while BIR increased (p < .05). Volume changes were similar among root repair materials and immersion media (p > .05). All materials supported PDLSC viability. TNF was upregulated only in NMTA2S with the 6-hour eluate. COL1A1 and SPP1 were upregulated in all groups exposed to the 6-hour eluate. With the 24-hour eluate, only BIR sustained COL1A1 signaling, and did not significantly express SPP1. With the 48-hour eluate, COL1A1 was upregulated in all groups along with ALPL.ConclusionDespite their longer setting times, NMTA2S and NMTA2R exhibited acceptable physicochemical and biological properties. Additionally, NMTA2S and NMTA2R appear to offer distinct advantages towards an osteogenic potential, which provides valuable insights for endodontic or reparative treatment choices.Clinical relevanceThis study provides the first evidence of osteogenic gene expression in PDLSCs by NeoMTA 2, as an endodontic sealer and root repair material. The findings highlight NeoMTA 2’s distinct biological response at different eluate time points, reinforcing its potential for endodontic and reparative applications.